Solubility of amino acids: a group-contribution model involving phase and chemical equilibria - Pinho, Simão (2010)
A new model is proposed to represent the solubility behavior of 14 amino acids and 5 small peptides in water. The UNIFAC model is combined with a Debye-Huckel term to describe the activity coefficients of the species present in the biomolecule/water system. New groups have been defined according to the group-contribution concept, and chemical equilibrium is taken into account simultaneously with the physical equilibrium. To estimate the new interaction parameters, molal activity coefficient data from the literature were used. These parameters, in addition to solubility data, were the basis for the correlation of the solubility product of the amino acids. Using this approach, satisfactory results were obtained in the representation and prediction of the solubilities of amino acids in aqueous solutions at different conditions of temperature and pH.